2011
DOI: 10.3390/ijerph8093528
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Networking and Addiction—A Review of the Psychological Literature

Abstract: Social Networking Sites (SNSs) are virtual communities where users can create individual public profiles, interact with real-life friends, and meet other people based on shared interests. They are seen as a ‘global consumer phenomenon’ with an exponential rise in usage within the last few years. Anecdotal case study evidence suggests that ‘addiction’ to social networks on the Internet may be a potential mental health problem for some users. However, the contemporary scientific literature addressing the addicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

39
1,104
2
127

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,574 publications
(1,272 citation statements)
references
References 88 publications
39
1,104
2
127
Order By: Relevance
“…However, unlike the hypothesised relationship, the use of social applications other than SNSs and Twitter did not contribute to predicting Internet addiction. A variety of studies have indicated that the excessive use of online social networking sites may be problematic (e.g., Kuss & Griffiths, 2011;Leung & Lee, 2012) as it tends to reinforce the establishment and maintenance of online, rather than offline, social networks. In a similar vein, excessive use of Twitter may have detrimental consequences for real life communication and is believed to activate the hedonistic dopamine system (Hofmann, Vohs, & Baumeister, 2012), that offers instantaneous gratification when using applications such as Twitter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike the hypothesised relationship, the use of social applications other than SNSs and Twitter did not contribute to predicting Internet addiction. A variety of studies have indicated that the excessive use of online social networking sites may be problematic (e.g., Kuss & Griffiths, 2011;Leung & Lee, 2012) as it tends to reinforce the establishment and maintenance of online, rather than offline, social networks. In a similar vein, excessive use of Twitter may have detrimental consequences for real life communication and is believed to activate the hedonistic dopamine system (Hofmann, Vohs, & Baumeister, 2012), that offers instantaneous gratification when using applications such as Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, excessive online gaming (Kuss & Griffiths, 2012b), excessive online gambling (Griffiths & Parke, 2010), and the use of social media (van den Eijnden, Meerkerk, Vermulst, Spijkerman, & Engels, 2008), such as online social networks (SNSs) (Kuss & Griffiths, 2011) appear to stand out. Their increasing diversity and usage growth among young populations (Entertainment Software Association, 2012;Lenhart, Purcell, Smith, & Zickuhr, 2012) is mirrored by the rising number of treatment studies (King, Delfabbro, Griffiths, & Gradisar, 2011;Liu, Liao, & Smith, 2012).…”
mentioning
confidence: 99%
“…FB allows individuals represent themselves using individual profiles and wall posts. Often, this provides connecting with real life friends and maintain the connections over time [58]. But having a fake FB account is a popular entity among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, given that Internet addiction is recognized worldwide as a challenge for modern society (e.g., [3], excessive Facebook use raises public concerns as well. This is mainly reflected in the rising number of publications on that subject [4,5].…”
Section: Introductionmentioning
confidence: 99%